Local Government Discretion and Accountability in Burkina Faso - Mahieu, S. (2012)
Burkina Faso opted for a progressive approach to decentralization reforms, aiming at building local government capacity first before transferring responsibilities. We employ a diagnostic framework to analyze local government discretion and accountability in Burkina Faso. We find that local governments have a very low degree of discretionary power accompanied with weak accountability towards citizens at all levels. In the political and administrative spheres, the center plays a dominant role in local government affairs leaving little space for discretion. In the fiscal sphere, taxing powers are restricted, while transfers are insufficient and unpredictable, making local financial management extremely difficult. Copyright (C) 2010 John Wiley & Sons, Ltd.